2019
DOI: 10.3389/fimmu.2019.01407
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and Skin Autoimmunity

Abstract: Several lines of evidence indicate that the immune system, inflammation, and coagulation are simultaneously activated in autoimmune and immune-mediated skin diseases. Pro-inflammatory cytokines such as interleukin-6 and tumor necrosis factor-alpha induce the expression of the main initiator of coagulation, i.e., tissue factor. The proteases of coagulation in turn act on protease-activated receptors inducing the expression of various pro-inflammatory cytokines triggering inflammation. The cross-talk among immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 158 publications
(195 reference statements)
0
22
0
1
Order By: Relevance
“…It has been consistently reported that the risk of thrombosis is increased in patients with BP [ 202 , 215 , 216 ]. Cugno and coworkers have focused on the relationships among immune response, inflammation, and blood coagulation in bullous pemphigoid [ 217 ]. As is known, the dermo-epidermal detachment is due to the interaction of autoAbs with BP180 and BP230 hemidesmosomal antigens, followed by complement activation and leukocyte infiltration.…”
Section: Predisposing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been consistently reported that the risk of thrombosis is increased in patients with BP [ 202 , 215 , 216 ]. Cugno and coworkers have focused on the relationships among immune response, inflammation, and blood coagulation in bullous pemphigoid [ 217 ]. As is known, the dermo-epidermal detachment is due to the interaction of autoAbs with BP180 and BP230 hemidesmosomal antigens, followed by complement activation and leukocyte infiltration.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Moreover, eosinophils strongly express tissue factor, which is the main initiator of the coagulation cascade (factors VII, X, VII, V, and prothrombin) leading to generation of thrombin [ 226 , 227 ]. This increases the permeability of blood vessels [ 228 ], thus favoring the transendothelial migration of inflammatory cells and their accumulation in the skin [ 217 ]. Neutrophils contribute to the pathogenesis of BP by releasing reactive oxygen species (ROS) and proteases.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Nonetheless, after tissue and vascular endothelium are damaged, and the physical barrier separating intravessel factor VII from TF is disrupted, the factor VII-TF complex is formed. Furthermore, during stimulation of monocytes, macrophages, and endothelial cells by endotoxins, cytokines, and lectins, the expression of TF increases in these cells in parallel with an increase in procoagulant activity [76]. In ACS, concentrations of inflammatory cytokines, such as TNF-α and interleukins, increase at the site of coronary artery occlusion to such an extent that TF is produced in vascular cells.…”
Section: Tissue Factor (Tf)mentioning
confidence: 99%
“… 2 . Though the pathogenesis of CSU remains unclear, autoimmunity, inflammation, coagulation and autoallergy might be related 3‐6 …”
Section: Introductionmentioning
confidence: 99%
“…2 Though the pathogenesis of CSU remains unclear, autoimmunity, inflammation, coagulation and autoallergy might be related. [3][4][5][6] It has recently been reported that CSU patients have increased risk of obesity or metabolic syndromes, 2,7 particularly dyslipidemia. 8 Serum cholesterol or low-density lipoprotein (LDL) levels in CSU patients are increased and correlated with disease severity.…”
Section: Introductionmentioning
confidence: 99%